Lane bias at the 2013 Swimming World Championships - Brammer, C.; Cornett, A.; Stager, J. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The Olympic Games and World Championships are the pinnacle of international sporting competitions where athletes compete in a wide variety of competitive events while representing their respective nations. However, as we watch these competitions, we do so under the assumption that each competitor's success is determined solely by hard work, commitment, discipline, and talent, and not influenced by external variables or biases. To ensure that this is so, international governing bodies, such as FINA, IAAF, FIFA, and the International Olympic Committee (IOC), exist to 'provide fair and drug free sport'. lt is unfortunate, however, that there are circumstances when external biases unfairly influence sporting outcomes, and can only be identified ex post facto when it's too late to protect the integrity of the competition. The most obvious and evident of these external biases involves the competitors' use of ergogenic substances to enhance their performance. Considerable effort and funding have been devoted specifically to curtail performance enhancing drug (PED) use, but the means to enforce the rules always seems to lag behind those used to disregard them (Botre 2008). Sport governing bodies must also consider advances in technology (e.g, equipment, uniforms, timekeeping) that sometimes challenge the inherent nature of the sport by unduly influencing competitive outcomes. For example, since the early 21st century, swimsuit manufacturers have experimented with different fabrics, shapes, and stitching techniques in an effort to provide competitive swimmers with the fastest swimwear. However, it was not until 2008 that a swimsuit innovation drastically biased Olympic competition in favor of those with access to them (Brammer et al. 2012). like PEDs, the suits facilitated a swimmer's intrinsic and natural ability to perform, and were subsequently banned in 2010. In 2010, design limitations were imposed by the sport's international governing body, the Federation lnternationale de Natation (FINA), to constrain competitive suit manufacturers as a means to re-establish competitive fairness. This example is particularly important because it demonstrates that performance data can be described using analytical techniques, which can then be used to identify the existence (or lack) of competition bias. Further, this empirical evidence can prompt sportgoverning bodies to act to remove the bias. This, the use of analytics to identify and remove competition bias, is the focus of this paper. A recent scenario at the 2013 FINA World Swimming Championships in Barcelona presents another opportunity to use analytics to identify variables potentially influencing competitive outcomes. According to observers and participants, a current was present in the pool such that when swimmingaway from the finishing end swimmers were at a competitive disadvantage on one side of the pool but at an advantage on the opposite side. If there was, in fact, a current in the pool during competition, it would have violated FIN A regulations which state that water flowing into and out of the pool is {permissible as long as no appreciable current or turbulence is created' (FINA, 2013, p. 392). Because the competitive venue was temporary, it is no longer possible to directly measure the flow characteristics of the pool. However, quantitative analysis of existing performance data might allow appropriate conclusions to be drawn. Thus, the purpose of this study was to use an analytical approach to assess the performance data from the 2013 FINA World Swimming Championships. This was done in order to determine whether or not evidence exists in support of the hypothesis that swimmers' competitive performances (and thus the race outcomes) were affected by lane assignment.